Natural Lyme disease cycles maintained via sheep by co-feeding ticks - Ogden, N; Nuttall, P; Randolph, S (Cambridge University Press, 1997)
We present observational and experimental evidence that cycles of the Lyme disease spirochaete, Borrelia burgdorferi S.1., can be maintained by sheep in the virtual absence of alternative hosts. A 2-year field study in upland moorland habitats of northwest UK established that sheep feed up to 80% of larval, >99% of nymphal and all of the adult female tick (Ixodes ricinus) population. Infection prevalence of B. burgdorferi in questing ticks reaches over 20%, but amplification of infection occurs principally as nymphs (20- to 30-fold), rather than larvae (4- to 7-fold), feed on sheep, and transmission from sheep to ticks occurred only during peak tick abundance in May and September. Experimental transmission studies confirmed that sheep, previously exposed to infected ticks on the moorland site, do not support systemic infections of B. burgdorferi, but they can transmit localized infections from infected to uninfected ticks co-feeding at the same site on the sheep's body.